Homeland - Doctorow, Cory. (New York : Tor Teen, 2013)
When Marcus, once called M1k3y, receives a thumbdrive containing evidence of corporate and governmental treachery, his job, fame, family, and well-being, as well as his reform-minded employer's election campaign, are all endangered.
"A Tom Doherty Associates Book."
Keywords: United States. -- Dept. of Homeland Security -- Fiction; Politics, Practical -- Fiction; Computer hackers -- Fiction; Civil rights -- Fiction; Counterculture -- Fiction; San Francisco (Calif.) -- Fiction